Construction and Deconstruction of a Homicide Reduction Policy: The Case of Pact for Life in Pernambuco, Brazil - Ratton, José Luiz; Daudelin, Jean (International Journal of Criminology and Sociology, 2018)
This paper tries to demonstrate that both the fall in homicides in Pernambuco (from 2007-2013) and the resurgence in them that followed (2014-2017) are fundamentally linked to two explanatory variables, which are in turn connected: the model of governance of public security produced in Pernambuco at the level of state government strategy and the capacity for deterrence produced in the framework of the Criminal Justice System (especially that of state police, who are under the responsibility and “control” of the executive power of the state). This article argues that the construction of this specific model of governance of Public Security and the definition, monitoring and realization of deterrence strategies within the police were crucial to the reduction of the number of homicides in the most violent areas of the state. On the other hand, the dissolution of the capacity for integrated governance of the police, with the consequent dismantling of the deterrence capacity aimed primarily at the reduction of homicides and crimes against life that had been successfully conceived and realized between 2007 and 2013, explains the increase in intentional violent crimes that has been observed since 2014.